Fluorimetric Determination of Rivastigmine in Rat Plasma by a Reverse Phase — High Performance Liquid Chromatographic Method - Karthik, Arumugam; Subramanian, Ganesa Sundarajan; Surulivelrajan, Mallayasamy; Ranjithkumar, Averineni; Kamat, Suresh B (Arzneimittelforschung, 2008)
A sensitive and selective high performance liquid chromatographic (HPLC) method was developed and validated for the rapid quantification of rivastigmine (CAS 123441-03-2) in micro quantity in rat plasma samples. The chromatographic separation was achieved with a reverse phase monomeric column C18 (4.6 × 250 mm, 5 µm) and the mobile phase consisted of acetonitrile and 20 mmol/L phosphate buffer pH 3.0 (25:75) with a flow rate of 1 mL/min. The effluents were measured by fluorimetric detection with excitation and emission wavelengths at 220 nm and 293 nm, respectively. The calibration curve was linear (r2 >0.99) ranging from 25–3000 ng/mL and the lower limit of quantification was 25 ng/mL. The method was validated with excellent sensitivity, selectivity, accuracy, precision, recovery and stability. The method has been successfully applied in a pharmacokinetic study of rivastigmine in rats.
Keywords: Acetylcholine esterase inhibitors; CAS 123441-03-2; Rivastigmine, bioanalytical method, fluorimetric detection, HPLC, rat plasma, validation